2022
DOI: 10.1111/bcpt.13731
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of glucagon after intravenous, intraperitoneal and subcutaneous administration in a pig model

Abstract: Introduction There is increasing scientific evidence to substantiate using low‐dose glucagon as a supplement to insulin therapy in artificial pancreata for diabetes mellitus type 1. The delivery of both these hormones intraperitoneally would mimic normal physiology. However, our knowledge of the pharmacological properties of glucagon after intraperitoneal administration is limited. This study compared the pharmacokinetics of glucagon after intraperitoneal, subcutaneous and intravenous administration and the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Unlike insulin, glucagon is absorbed rapidly after SC administration, reaching maximum plasma concentrations in humans at approximately 10-20 min (Simmons and Williams, 1992;Graf et al, 1999;El-Khatib et al, 2010;El Youssef et al, 2014;Blauw et al, 2016;Castle et al, 2016;Ranjan et al, 2016;Hövelmann et al, 2018;Hövelmann et al, 2019). Previous animal trials conducted by our research group demonstrated no significant difference in the absorption speed or glucose elevating effect of glucagon after SC compared to intraperitoneal administration (Dirnena-Fusini et al, 2018;Åm et al, 2020;Teigen et al, 2022). This observation contrasts with the major delay in insulin absorption and effect after SC administration compared to intraperitoneal administration (Christiansen et al, 2017).…”
Section: Vasodilatory Effects Of Sc Microdoses Of Glucagonmentioning
confidence: 66%
See 1 more Smart Citation
“…Unlike insulin, glucagon is absorbed rapidly after SC administration, reaching maximum plasma concentrations in humans at approximately 10-20 min (Simmons and Williams, 1992;Graf et al, 1999;El-Khatib et al, 2010;El Youssef et al, 2014;Blauw et al, 2016;Castle et al, 2016;Ranjan et al, 2016;Hövelmann et al, 2018;Hövelmann et al, 2019). Previous animal trials conducted by our research group demonstrated no significant difference in the absorption speed or glucose elevating effect of glucagon after SC compared to intraperitoneal administration (Dirnena-Fusini et al, 2018;Åm et al, 2020;Teigen et al, 2022). This observation contrasts with the major delay in insulin absorption and effect after SC administration compared to intraperitoneal administration (Christiansen et al, 2017).…”
Section: Vasodilatory Effects Of Sc Microdoses Of Glucagonmentioning
confidence: 66%
“…This observation contrasts with the major delay in insulin absorption and effect after SC administration compared to intraperitoneal administration ( Christiansen et al, 2017 ). Therefore, we hypothesise that the local vasodilatory effect of glucagon promotes its absorption from the SC space, as this would explain why there is no significant difference in absorption or the time to onset and maximum effect of SC versus intraperitoneally delivered glucagon ( Teigen et al, 2022 ).…”
Section: Vasodilatory Effects Of Sc Micro-doses Of Glucagonmentioning
confidence: 99%
“…The values of T max and T 1/2 of glucagon were comparable to observations in a previous pig study we have performed that investigated glucagon pharmacokinetics. 15 As such, the absorption and elimination time of glucagon did not seem to be influenced by insulin being deposited at the same subcutaneous site. No local adverse reactions on the skin were observed during the insulin and glucagon infusions.…”
Section: Discussionmentioning
confidence: 81%
“…It is therefore not surprising that there seems to be a considerable first-pass metabolism of glucagon in the liver; that is, that a large proportion of glucagon is extracted (and utilized) upon passing the liver and that only a small fraction reaches systemic circulation. 15 If this first-pass effect is saturable, as we have previously hypothesized, 16 microdoses of glucagon administered with mealtime insulin are probably less likely to cause postprandial glucose excursions because the liver will already be saturated with glucagon. This would have to be investigated in patients with DM1.…”
Section: Discussionmentioning
confidence: 96%